Effectiveness of the System Usability Scale in Identifying Usability Issues A Systematic Literature Review - Radhi Rabbani; Dwi Yuniarto; Yayan Cahyan (Jurnal Intelek Insan Cendikia, 2026)
Usability measurement is a crucial software quality indicator, yet the popular System Usability Scale (SUS) instrument has limitations in diagnosing specific interface issues. This study aims to analyze the role, score interpretation, effectiveness, and contribution of SUS to problem identification and interface design improvement. The methodology employed is a Systematic Literature Review (SLR) based on Kitchenham's guidelines and PRISMA standards, analyzing 33 primary studies (yielding 35 evaluation datasets) from Google Scholar, IEEE Xplore, and SINTA databases. The findings indicate an average SUS score of 68.04, placing system usability at the Marginal-Acceptable threshold. All reviewed studies confirm that SUS does not directly pinpoint problem sources, functioning solely as a global perception indicator, while specific issues are uncovered through complementary qualitative methods such as Think Aloud, observations, and interviews. Furthermore, while 84.8% of the studies formulated user interface redesign recommendations, a validation gap exists, as only 6.1% (2 studies) conducted retesting. In conclusion, SUS is highly effective as a validation tool for final user perception, but it must be integrated complementarily with qualitative methods and iterative testing approaches to achieve a comprehensive usability evaluation.